Culinary Innovation Made from Oyster Mushroom: The Process of Mentoring and Nugget Creation as a Business Opportunity for Local MSMEs - Rika Febriyani; Hamka; Sahiruddin (Economics and Business Journal (ECBIS), 2026)
Oyster mushrooms (Pleurotus ostreatus) are agricultural commodities with high economic value with good nutritional content. Its cultivation in Jumantoro Village, Jumapolo District, Karanganyar Regency, has great potential because it is supported by suitable natural conditions. However, farmers and MSMEs still face obstacles in the use of manual equipment and less than optimal marketing, so product innovation is needed to increase the added value and competitiveness of oyster mushrooms in the market. As a solution, a mentoring program was introduced with the culinary innovation of oyster mushroom nuggets. This activity includes surveys and interviews with MSMEs, transfer of cultivation knowledge, and production practices. Nuggets were chosen because their texture resembles chicken meat, making them an economical and healthy food alternative. Production is carried out at the MSME's Mushroom House with a systematic method to ensure quality. The results of the mentoring showed a positive response from MSMEs and the community, both in terms of economy and product acceptance. In addition to increasing local income, this program also provides direct experience for students in understanding mushroom cultivation and processing. By optimizing local potential, innovation in processed oyster mushroom products can be a sustainable strategy in supporting village economic growth.